Enhancing the dependability of human-machine systems using brunswikian symmetry - Jipp, Meike; Badreddin, Essameddin (International Conference on Computational Intelligence for Modelling, Control and Automation, 2006 and International Conference on Intelligent Agents, Web Technologies and Internet Commerce, 2006)
Brunswikian theory and the symmetry principle of information accessibility and processing are introduced to analyze the interaction between a technical system and their users on the example of an intelligent expert help system for a photocopy machine. To improve the interaction and thus to increase the system's dependability, symmetry must be achieved in information accessibility and processing by generalizing the design-by-contract approach to human-machine interaction. Balancing asymmetry will enable more dependable man-machine systems.
Gesehen am 11.12.2019